PENGAWASAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) PROVINSI RIAU (STUDI KASUS KORBAN KDRT DI KOTA PEKANBARU) - Yanti, Evi; Khairani, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research intent to analyse and words observation that done by P2TP2A Riau's Province about KDRT'S case handle that happening and about performance which they do. violence to female is each conduct base distinctive get ensuing gender basis misery or female grief physically, sexual, or psychological. Empowerments coherent service station female And Child constitute one of ministering mode form for female and child that even out service coherenting to cover prevention, penyediaan, and coherent service management for victim covers reabilitasi social's service, legal aid and pemantaun and evaluation. About problem which is worked through deep this paper which is how coherent Service Station role female Empowerment And Child on one's guard violence which happens and whatever one become faced constraint Empowerments coherent Service Station female And Child in do observation to violence that experienced by female and child. this research utilizes analisis kualitatif deskriftif. Result observationaling to point out that observation to victim that experience violence well that violence to female and violence to masing's child adverse. It visually of yielding researcher interview with exhaustive informan whatever available which is haven't available socialization is done. Factor is factor that regard that observation which is minim available SDM it, hall situation that doesn't back up and facility that really subtracted. There is tips even on observational it that P2TP2A does socialization to society and government also want engaged help for penangan case that experienced by gives what do be needed so task which will do P2TP2A more effective.Key word: P2TP2A'S Riau's, KDRT